Current collector and preparation method thereof, positive pole piece, secondary battery and electric device

A polydioxolane-coated current collector addresses the corrosion issue in aluminum foil by preventing electrolyte contact, improving battery safety and cycle life.

CN119230836AActive Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310791353.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31
Estimated Expiration
2043-06-29

AI Technical Summary

Technical Problem

The existing aluminum foil current collectors in lithium-ion batteries are prone to corrosion due to interaction with electrolytes at high voltages, leading to safety issues and reduced cycle life.

Method used

A current collector with a protective coating made of polydioxolane, optionally containing lithium salts and sulfonic acid groups, which provides mechanical flexibility and prevents electrolyte contact, thereby protecting the substrate from corrosion.

Benefits of technology

The protective coating enhances battery safety and extends cycle life by preventing substrate corrosion and maintaining structural integrity under high pressure and density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230836A_ABST
    Figure CN119230836A_ABST
Patent Text Reader

Abstract

The invention provides a current collector and a preparation method thereof, a positive pole piece, a secondary battery and an electric device, the current collector comprises a base material and a protective coating located on at least one side of the base material, and the protective coating comprises polydioxolame; the protective coating is uniform and compact and has good mechanical flexibility; on one hand, the protective coating can effectively protect the base material under high pressure density so as to reduce and even avoid cracking of an oxidation film on the surface of the base material, and on the other hand, the protective coating can prevent direct contact between electrolyte and the base material and inhibit the electrolyte from corroding the base material, so that the safety and the service life of the secondary battery are improved through the comprehensive action.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a current collector and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device. Background Art

[0002] The current collector is a key component in the battery and directly determines the cycle life and performance of the battery. The ideal current collector should first have sufficient electronic conductivity. In addition, the current collector should also have stable chemical and electrochemical properties to adapt to various working environments of different battery systems.

[0003] In the related art, the positive electrode current collector is mostly made of aluminum foil, but the stability of aluminum foil in lithium-ion electrolyte is poor, and the naturally formed Al2O3 surface is not enough to resist the corrosion of the electrolyte. Especially under high voltage exceeding 3.0V, the lithium salts in the electrolyte, such as LiPF6, LiClO4, LiFSI and LiTFSI, will corrode the aluminum foil and oxidize it into Al 3+ The ions dissolve into the electrolyte, causing the aluminum foil to break, leading to battery safety problems. Summary of the invention

[0004] Based on this, it is necessary to provide a current collector and a preparation method thereof, a positive electrode sheet, a secondary battery and an electrical device to improve the corrosion of the electrolyte to the current collector substrate and improve the battery safety.

[0005] In order to achieve the above-mentioned object, the first aspect of the present application provides a current collector, comprising:

[0006] substrate; and

[0007] A protective coating is disposed on at least one side of the substrate, wherein the protective coating comprises polydioxolane.

[0008] The current collector of the present application has a protective coating containing polydioxolane, which is uniform and dense and has good mechanical flexibility. On the one hand, the protective coating can effectively protect the substrate under high pressure and density to reduce or even avoid the rupture of the oxide film on the surface of the substrate. On the other hand, the protective coating can also prevent the electrolyte from directly contacting the substrate and inhibit the electrolyte from corroding the substrate. The above-mentioned comprehensive effects improve the safety and life of the secondary battery.

[0009] In some embodiments, the protective coating further comprises lithium ions and at least one of a sulfonic acid group and a sulfonic acid-like group, wherein the lithium ions form a lithium salt with at least one of the sulfonic acid group and the sulfonic acid-like group;

[0010] Optionally, the mass proportion of the lithium salt in the protective coating is 0.5%-8%, optionally 2%-5%.

[0011] Optionally, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium bis(pentafluoroethanesulfonyl)imide.

[0012] In some embodiments, the protective coating has a thickness of 50 nm-800 nm, and may be 300 nm-500 nm.

[0013] In some embodiments, the mass proportion of the polydioxolane in the protective coating is 92%-99.5%, and optionally 95%-98%.

[0014] In some embodiments, aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is charge attraction between the aluminum ions and a surface of the protective coating adjacent to the substrate.

[0015] In some embodiments, the current collector further comprises a pre-coating layer;

[0016] Optionally, the pre-coating layer comprises at least one of the following features:

[0017] (1) The pre-coating layer is located between the substrate and the protective coating layer;

[0018] (2) the pre-coating layer is located between the substrate and the protective coating layer, aluminum ions are adsorbed at the interface between the pre-coating layer and the protective coating layer, and there is a charge adsorption effect between the aluminum ions and the surface of the protective coating layer adjacent to the pre-coating layer;

[0019] (3) The pre-coating layer is located on a side of the protective coating layer away from the substrate;

[0020] (4) The pre-coating layer is located on a side of the protective coating layer away from the substrate, aluminum ions are adsorbed at the interface between the substrate and the protective coating layer, and there is a charge attraction between the aluminum ions and a surface of the protective coating layer adjacent to the substrate.

[0021] In some embodiments, the pre-coating layer comprises a carbon coating;

[0022] Optionally, the material of the carbon coating has at least one of the following characteristics:

[0023] (1) The thickness of the carbon coating is 1 μm-10 μm, and can be 1 μm-5 μm;

[0024] (2) The carbon coating comprises a first conductive agent and a first binder;

[0025] Optionally, the mass ratio of the first conductive agent to the first bonding agent is (1-19):1;

[0026] Optionally, the first conductive agent includes one or more of superconducting carbon fiber, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers;

[0027] Optionally, the first binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0028] In some embodiments, the pre-coating layer comprises an active particle coating;

[0029] Optionally, the active particle coating has at least one of the following characteristics:

[0030] (1) The thickness of the active particle coating is 2 μm-20 μm;

[0031] (2) The active particle coating comprises active material particles, a second conductive agent and a second binder;

[0032] Optionally, the volume average particle size Dv50 of the active material particles is 0.2 μm-4 μm;

[0033] Optionally, the mass ratio of the active material particles, the second conductive agent and the second binder is (50-80):(10-30):(10-20);

[0034] Optionally, the second conductive agent includes one or more of superconducting carbon fiber, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers;

[0035] Optionally, the second binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0036] The second aspect of the present application provides a method for preparing the current collector of the first aspect of the present application, comprising the following steps:

[0037] A solution A containing an etchant and a solution B containing 1,3-dioxolane are prepared respectively; the solution B further contains one or more of a sulfonic acid group and a sulfonic acid-like group;

[0038] The solution A is coated on at least one side of the surface of the substrate precursor and then etched to prepare the substrate;

[0039] Solution B is coated on the surface of the etched substrate precursor to prepare the current collector.

[0040] In some embodiments, the solution A comprises at least one of the following conditions:

[0041] (1) The etchant comprises a fluorinated aluminum sulfonate;

[0042] Optionally, the fluorine-containing aluminum sulfonate salt includes one or more of aluminum trifluoromethanesulfonate, aluminum perfluorobutanesulfonate, and aluminum bistrifluoromethanesulfonimide;

[0043] (2) The mass proportion of the fluorinated aluminum sulfonate in the solution A is 2%-5%;

[0044] (3) The solvent of the solution A includes one or more of 1,2-dimethoxyethane, diethyl ether, acetone and acetonitrile.

[0045] In some embodiments, the solution B further comprises lithium ions, and the lithium ions form a lithium salt with at least one of the sulfonic acid group and the sulfonic acid-like group;

[0046] Optionally, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium bis(pentafluoroethanesulfonyl)imide;

[0047] Optionally, the mass proportion of the lithium salt in the solution B is 2%-5%.

[0048] In some embodiments, the etching time is 5 min-30 min.

[0049] The third aspect of the present application provides a positive electrode plate, comprising the current collector of the first aspect of the present application or the current collector prepared by the method of the second aspect of the present application.

[0050] A fourth aspect of the present application provides a secondary battery, which includes the positive electrode sheet of the third aspect of the present application.

[0051] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 It is a schematic diagram of a current collector according to one embodiment of the present application.

[0053] Figure 2 It is a schematic diagram of a current collector according to one embodiment of the present application.

[0054] Figure 3 It is a schematic diagram of a current collector according to one embodiment of the present application.

[0055] Figure 4 is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0056] Figure 5 yes Figure 4 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0057] Figure 6 FIG. 1 is a schematic diagram of an electric device using a secondary battery according to an embodiment of the present application as a power source.

[0058] Description of reference numerals:

[0059] 1 secondary battery; 11 housing; 12 electrode assembly; 13 cover plate; 2 power-consuming device. DETAILED DESCRIPTION

[0060] In order to facilitate the understanding of the present application, the present application will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present application are given in the drawings. However, the present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0061] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.

[0062] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0063] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0064] In this application, when referring to the unit of a data range, if there is a unit only after the right endpoint, it means that the units of the left endpoint and the right endpoint are the same. For example, 10-1000nm means that the units of the left endpoint "10" and the right endpoint "1000" are both nm (nanometers).

[0065] In this application, "multiple", "multiple", "multiple times" and the like, unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "multiple" means greater than or equal to two. Only some numerical ranges are specifically disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and similarly any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, each separately disclosed point or single value itself can be combined as a lower limit or upper limit with any other point or single value or with other lower limits or upper limits to form an unambiguous range.

[0066] The "range" disclosed in this application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values.

[0067] The temperature parameters in this application, unless otherwise specified, allow for both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range of instrument control.

[0068] In the related art, when aluminum foil is used as the positive electrode current collector, the naturally formed Al2O3 surface is not enough to resist the corrosion of the electrolyte. Especially under high voltage exceeding 3.0V, the lithium salt in the electrolyte will corrode the aluminum foil and oxidize it into Al 3+ The ions dissolve into the electrolyte, causing the aluminum foil to break, leading to battery safety problems.

[0069] In addition, aluminum foil as a cathode current collector needs to have high electronic conductivity to allow considerable current to flow through the highly loaded cathode.

[0070] At the same time, in order to meet the energy density requirements, the compaction density of the positive electrode sheet is getting higher and higher, generally increased to 3.5g / cm 3 As mentioned above, under high-pressure dense roller pressing, the oxide film on the surface of the current collector is easily damaged, resulting in exposure of fresh aluminum and accelerated corrosion of the aluminum foil.

[0071] Based on the above problems, the present application provides a current collector including a substrate and a protective coating, wherein the material of the protective coating includes a polymer polydioxolane, and the protective coating containing polydioxolane is uniform and dense and has good mechanical flexibility; on the one hand, the protective coating can effectively protect the substrate under high pressure and density to reduce or even avoid the rupture of the oxide film on the surface of the substrate, and on the other hand, the protective coating can also prevent the electrolyte from directly contacting the substrate, inhibiting the corrosion of the substrate by the electrolyte, thereby improving the safety and life of the secondary battery.

[0072] A first aspect of the present application provides a current collector, comprising a substrate and a protective coating located on at least one side of the substrate, wherein the protective coating comprises polydioxolane.

[0073] It should be noted that the protective coating may be located on only one side of the substrate, or may be located on both sides of the substrate at the same time; preferably, the protective coating is located on both sides of the substrate at the same time.

[0074] The structural formula of polydioxolane is as follows:

[0075]

[0076] The value range of n is 100-5000.

[0077] Understandably, during the preparation of the protective coating, an etchant is first added to etch the surface of the substrate. On the surface of the substrate, a large amount of 1,3-dioxolane undergoes ring-opening polymerization under the catalysis of sulfonic acid groups or quasi-sulfonic acid groups. The ring-opened 1,3-dioxolane can be evenly connected and polymerized into a film in a direction perpendicular to the substrate, which is macroscopically uniform and dense. The polydioxolane prepared after ring-opening polymerization is a long-chain structure. In an ideal state, the long chain of polydioxolane is perpendicular to the surface of the substrate, but in actual conditions, the long chain of polydioxolane is not perpendicular to the substrate, and the long-chain structure makes the internal molecules of the protective coating have good flexibility, which can withstand the mechanical stress at high pressure density and play a buffering and protective role on the substrate. The current collector of the present application includes a protective coating, and the material of the protective coating includes polydioxolane. The protective coating is uniform and dense and has good mechanical flexibility. On the one hand, the protective coating can effectively protect the substrate under high pressure density to reduce or even avoid the rupture of the oxide film on the surface of the substrate. On the other hand, the protective coating can also prevent the electrolyte from directly contacting the substrate and inhibit the electrolyte from corroding the substrate. The safety and life of the secondary battery are improved through the above-mentioned comprehensive effects.

[0078] As an example, the polymer contained in the above-mentioned protective coating can be qualitatively analyzed by infrared or Raman spectroscopy, nuclear magnetic hydrogen spectroscopy, thermogravimetric analysis and other detection methods.

[0079] Figure 1 A schematic diagram of the structure of a current collector improved in one implementation mode; Figure 2 In the embodiment, the current collector includes a substrate 111 and a protective coating 112 , and the protective coating 112 is located on both sides of the substrate 111 .

[0080] In some embodiments, the protective coating further comprises lithium ions and at least one of sulfonic acid groups and sulfonic acid-like groups. The lithium ions and at least one of the sulfonic acid groups and sulfonic acid-like groups form lithium salts. Due to the presence of the lithium salts, lithium ions can be slowly released during the operation of the battery, thereby improving the battery life. Meanwhile, during the preparation of the protective coating, the sulfonic acid groups and sulfonic acid-like groups can catalyze the ring-opening polymerization of 1,3-dioxolane.

[0081] In some optional embodiments, the mass proportion of lithium salt in the protective coating is 0.5%-8%; when the mass proportion of lithium salt in the protective coating is lower than the above range, insufficient catalytic reaction may result, and 1,3-dioxolane may be difficult to polymerize into chains; when the mass proportion of lithium salt in the protective coating is higher than the above range, too much lithium salt may exist in the protective coating in the form of crystalline particles, affecting the overall flexibility of the protective coating. As an example, the mass proportion of lithium salt in the protective coating can be but is not limited to 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8% or a range between any two of the above values. Optionally, the mass proportion of lithium salt in the protective coating is 2%-5%.

[0082] It should be noted that when the current collector is prepared into a secondary battery, since the lithium salt slowly releases lithium ions during the operation of the secondary battery, the mass percentage of lithium ions or lithium salts in the protective coating is variable as the secondary battery is charged and discharged. The mass percentage of lithium salt in the protective coating mentioned above refers to the mass percentage of lithium salt contained in the current collector before it is used to prepare a secondary battery.

[0083] As an example, the mass proportion of the above-mentioned lithium salt in the protective coating can be determined by the following method: the substrate with the protective coating is immersed in an appropriate amount of deionized water, and after accelerated dissolution through processes such as ultrasound and stirring, the lithium salt content is determined by ion chromatography.

[0084] In some optional embodiments, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium bis(pentafluoroethanesulfonyl)imide. It should be noted that the anion contained in the lithium salt can catalyze the ring-opening polymerization of 1,3-dioxolane as a sulfonic acid-like group.

[0085] As a possible implementation, the thickness of the protective coating is 50nm-800nm; when the thickness of the protective coating is lower than the above range, it is difficult to prepare and has poor uniformity; when the thickness of the protective coating is higher than the above range, the internal impedance of the battery cell may increase due to insufficient conductivity of the protective coating, and it will occupy the limited space inside the battery cell, affecting the electrical performance of the battery cell. As an example, the thickness of the protective coating can be but is not limited to 50nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm ​​or a range between any two of the above values. Optionally, the thickness of the protective coating is 300nm-500nm.

[0086] It should be noted that the thickness of the protective coating mentioned above refers to the thickness of the protective coating located on one side of the substrate; when both sides of the substrate have protective coatings, the total thickness of the protective coating is the sum of the thicknesses of the protective coatings on both sides.

[0087] As an example, the thickness of the protective coating mentioned above can be measured using a high magnification scanning electron microscope.

[0088] In some embodiments, the mass proportion of polydioxolane in the protective coating is 92%-99.5%; for example, it can be but not limited to 92%, 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, 99.5% or the range between any two of the above values. When the mass proportion of polydioxolane in the protective coating is lower than the above range, it may cause the mass proportion of lithium salt in the protective coating to be relatively too large, affecting the overall flexibility of the protective coating; when the mass proportion of polydioxolane in the protective coating is higher than the above range, it may cause the mass proportion of lithium salt in the protective coating to be relatively too small, the catalytic reaction is insufficient, and 1,3-dioxolane is difficult to polymerize into chains. Optionally, the mass proportion of polydioxolane in the protective coating is 95%-98%.

[0089] As an example, the mass proportion of the above-mentioned polydioxolane in the protective coating can be quantitatively analyzed using infrared or Raman spectroscopy, nuclear magnetic hydrogen spectroscopy, thermogravimetric analysis and other detection methods.

[0090] In some embodiments, aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is charge attraction between the aluminum ions and the surface of the protective coating adjacent to the substrate.

[0091] It should be noted that aluminum ions are adsorbed on the substrate. The aluminum ions on the substrate are obtained by etching the substrate with an etchant containing aluminum ions. After etching, the aluminum ions can be evenly distributed on the substrate. There is a charge attraction between the aluminum ions and the surface of the protective coating adjacent to the substrate. The aluminum ions can electrostatically connect the substrate and the protective coating to improve the bonding strength between the substrate and the protective coating. At the same time, by etching the surface of the substrate to present an uneven pit shape, its surface smoothness is greatly reduced, and there is a strong surface interaction between the substrate and the protective coating, which further increases the bonding strength between the protective coating and the substrate. The good combination between the protective coating and the substrate can, on the one hand, prevent the positive electrode material from breaking or peeling off, and reduce the impedance increase of the cycle process; on the other hand, it can also play a supporting role to prevent the positive electrode active material layer from breaking during processing.

[0092] As a possible implementation manner, the material of the substrate includes one of aluminum foil, nickel foil and titanium-nickel alloy or Eucommia ulmoides.

[0093] In some possible implementations, the current collector further includes a pre-coating layer. The relative positions of the pre-coating layer and the protective coating layer are not limited; the pre-coating layer can further reduce or even avoid the damage of the positive electrode active particles to the substrate under high pressure density, and enhance the anti-corrosion protection effect of the substrate.

[0094] In some optional embodiments, the pre-coating layer is located between the substrate and the protective coating layer; the pre-coating layer can also prevent the etchant from over-etching the Al2O3 surface of the aluminum foil itself. It should be noted that in practical applications, when the protective coating layer is prepared on the surface of the pre-coating layer, the raw material solution of the protective coating layer can penetrate into the pores of the pre-coating layer to enhance the protective effect on the substrate.

[0095] In some optional embodiments, the pre-coating layer is located between the substrate and the protective coating layer, aluminum ions are adsorbed at the interface between the pre-coating layer and the protective coating layer, and there is a charge adsorption effect between the aluminum ions and the surface of the protective coating layer adjacent to the pre-coating layer.

[0096] It should be noted that aluminum ions are adsorbed on the pre-coating layer. The aluminum ions on the pre-coating layer are obtained by etching the pre-coating layer with an etchant containing aluminum ions. After etching, the aluminum ions can be evenly distributed on the pre-coating layer. Since there is a charge attraction between the aluminum ions and the surface of the protective coating layer adjacent to the pre-coating layer, the aluminum ions can electrostatically connect the pre-coating layer and the protective coating layer, thereby improving the bonding strength between the pre-coating layer and the protective coating layer. At the same time, the surface of the pre-coating layer is etched to present an uneven pit shape, and its surface smoothness is greatly reduced. There is a strong surface interaction between the pre-coating layer and the protective coating layer, which further increases the bonding strength between the protective coating layer and the pre-coating layer. The good bonding between the protective coating layer and the pre-coating layer can, on the one hand, prevent the positive electrode active material from breaking or peeling off, and reduce the impedance increase of the cycle process; on the other hand, it can also play a supporting role to prevent the positive electrode active material layer from breaking during processing.

[0097] In some optional embodiments, the pre-coating layer is located on the side of the protective coating layer away from the substrate.

[0098] In some optional embodiments, the pre-coating layer is located on the side of the protective coating layer away from the substrate, aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is charge attraction between the aluminum ions and the surface of the protective coating layer adjacent to the substrate.

[0099] It should be noted that aluminum ions are adsorbed on the substrate. The aluminum ions on the substrate are obtained by etching the substrate with an etchant containing aluminum ions. After etching, the aluminum ions can be evenly distributed on the substrate. Since there is a charge attraction between the aluminum ions and the surface of the protective coating adjacent to the substrate, the aluminum ions can electrostatically connect the substrate and the protective coating, thereby improving the bonding strength between the substrate and the protective coating. At the same time, by etching the surface of the substrate to present an uneven pit shape, its surface smoothness is greatly reduced, and there is a strong surface interaction between the substrate and the protective coating, further increasing the bonding strength between the protective coating and the substrate. The good bonding between the protective coating and the substrate can, on the one hand, prevent the positive electrode material from breaking or peeling off, and reduce the impedance increase of the cycle process; on the other hand, it can also play a supporting role to prevent the positive electrode active material layer from breaking during processing.

[0100] As a possible implementation, the pre-coating layer includes a carbon coating layer. On the one hand, using the carbon coating layer as a pre-coating layer can further improve the conductivity of the current collector. On the other hand, the particle size of the small solid particles in the carbon coating layer is much smaller than the particle size of the solid phase in the negative electrode film layer in the negative electrode sheet. The carbon coating layer is located between the substrate and the negative electrode film layer, which can reduce the pressure damage to the substrate surface caused by large particles in the negative electrode film layer during cold pressing.

[0101] Figure 2 A schematic diagram of the structure of a current collector provided in one embodiment; Figure 2 In the embodiment, the current collector includes a substrate 211, a carbon coating 212 respectively located on both sides of the substrate 211, and a protective coating 213 respectively located on both sides of the substrate 211; for the carbon coating 212 and the protective coating 213 on the same side of the substrate 211, the carbon coating 212 is located between the substrate 211 and the protective coating 213.

[0102] It should be noted that Figure 2 It is only a schematic structure of the current collector and should not be understood as a limitation on the relative positional relationship between the carbon coating and the protective coating in the current collector.

[0103] In some optional embodiments, the thickness of the carbon coating is 1 μm-10 μm; when the thickness of the carbon coating is lower than the above range, it is difficult to prepare and cannot be coated evenly; when the thickness of the carbon coating is higher than the above range, it will occupy the limited space inside the battery, resulting in a loss of battery energy density. As an example, the thickness of the carbon coating can be but is not limited to 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range between any two of the above values. Optionally, the thickness of the carbon coating is 1 μm-5 μm.

[0104] It should be noted that the thickness of the carbon coating mentioned above refers to the thickness of the carbon coating on one side of the substrate; when both sides of the substrate have carbon coatings, the total thickness of the carbon coating is the sum of the thicknesses of the carbon coatings on both sides.

[0105] As an example, the thickness of the above-mentioned carbon coating can be measured using a scanning electron microscope.

[0106] In some optional embodiments, the carbon coating comprises a first conductive agent and a first binder; it should be noted that the "first conductive agent" and "first binder" mentioned in this application are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.

[0107] In some optional embodiments, the mass ratio of the first conductive agent to the first binder in the carbon coating is (1-19):1; for example, it can be but not limited to 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1 or a range between any two of the above values. When the mass ratio of the first conductive agent to the first binder in the carbon coating is within the above range, the conductivity and adhesion of the carbon coating can be taken into account.

[0108] As an example, the mass ratio of the first conductive agent to the first binder in the above-mentioned carbon coating layer can be measured by thermogravimetric analysis.

[0109] In some optional embodiments, the first conductive agent includes one or more of superconducting carbon fiber, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. When the above substances are used as the first conductive agent in the carbon coating, the solid phase components in the carbon coating are small particles and micro beads, and the binder is more evenly dispersed in the carbon coating, and the contact between the binder and the substrate or the protective coating is more sufficient, which can further prevent the positive electrode active material from breaking or peeling off; it can also further play a supporting role to prevent the positive electrode active material layer from breaking during processing.

[0110] In some optional embodiments, the first binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0111] As a possible implementation, the pre-coating layer includes an active particle coating; on the one hand, the active particle coating contains active material particles, which can simultaneously exert the capacity and alleviate the excessive decrease in battery capacity caused by the provision of the protective coating and the pre-coating layer; on the other hand, the particle size of the small solid particles in the active particle coating is much smaller than the particle size of the solid phase in the negative electrode film layer in the negative electrode sheet. The active particle coating is located between the substrate and the negative electrode film layer, which can reduce the large particles in the negative electrode film layer from causing pressure damage to the substrate surface during cold pressing.

[0112] Figure 3 A schematic diagram of the structure of a current collector provided in one embodiment; Figure 3 In the embodiment, the current collector includes a substrate 311, an active particle coating 312 respectively located on both sides of the substrate 311, and a protective coating 313 respectively located on both sides of the substrate 311; for the active particle coating 312 and the protective coating 313 on the same side of the substrate 311, the active particle coating 312 is located between the substrate 311 and the protective coating 313.

[0113] It should be noted that Figure 3 It is only a schematic structure of the current collector and should not be understood as a limitation on the relative positional relationship between the active particle coating and the protective coating in the current collector.

[0114] In some optional embodiments, the thickness of the active particle coating is 2 μm-20 μm; for example, it can be but not limited to 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm or a range between any two of the above values. When the thickness of the active particle coating is lower than the above range, it is difficult to prepare and cannot be evenly coated; when the thickness of the active particle coating is higher than the above range, it will occupy the limited space inside the battery, resulting in a loss of battery energy density.

[0115] It should be noted that the thickness of the active particle coating mentioned above refers to the thickness of the active particle coating located on one side of the substrate; when both sides of the substrate have active particle coatings, the total thickness of the active particle coating is the sum of the thicknesses of the carbon coatings on both sides.

[0116] As an example, the thickness of the active particle coating mentioned above can be measured using a scanning electron microscope.

[0117] In some optional embodiments, the active particle coating comprises active material particles, a second conductive agent and a second binder; it should be noted that the "second conductive agent" and "second binder" mentioned in this application are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features.

[0118] In some optional embodiments, the volume average particle size Dv50 of the active material particles in the active particle coating is 0.2μm-4μm; when the volume average particle size Dv50 of the active material particles is lower than the above range, the slurry processing is difficult and easy to gel during the preparation of the active particle coating; when the volume average particle size Dv50 of the active material particles is higher than the above range, it is easy to cause pressure damage to the substrate and cannot play a protective role. As an example, the volume average particle size Dv50 of the active material particles can be but is not limited to 0.2μm, 0.5μm, 0.7μm, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, 2.2μm, 2.5μm, 2.8μm, 3μm, 3.2μm, 3.5μm, 3.7μm, 4μm or a range between any two of the above values.

[0119] As an example, the volume average particle size Dv50 of the active material particles mentioned above can be measured by the following method: wipe off and collect the coating on the active particles, burn off the conductive agent and the binder at high temperature, and test with a laser particle size analyzer to obtain the particle size distribution and volume average particle size Dv50 of the active material particles.

[0120] In some optional embodiments, the mass ratio of the active material particles, the second conductive agent and the second binder in the active particle coating is (50-80): (10-30): (10-20); for example, it can be but not limited to (55-80): (10-25): (10-18), (60-80): (10-20): (10-15), (65-80): (15-20): (10-15), (70-80): (15-20): (10-13) or a range between any two of the above ratios. When the mass ratio of the active material particles, the second conductive agent and the second binder is within the above range, the adhesion and conductivity of the active particle coating and the processability of the slurry during the coating preparation can be taken into account; at the same time, the active particle coating contains an appropriate amount of active material particles, which can prevent the excessive deterioration of the energy density of the battery cell caused by setting the coating.

[0121] As an example, the mass ratio of the active material particles, the second conductive agent and the second binder in the above-mentioned active particle coating can be determined by the following method: first, the type of active material particles is determined by element scanning, and the mass proportion of the active material particles is roughly determined according to the collector capacity; then, thermogravimetric analysis is used to roughly quantitatively calculate the second binder, and the remaining part is the mass proportion of the conductive agent; finally, the mass ratio of the three in the active particle coating is calculated.

[0122] In some optional embodiments, the second conductive agent includes one or more of superconducting carbon fibers, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.

[0123] In some optional embodiments, the second binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0124] In some optional embodiments, the active material particles may include at least one of the following materials: olivine-structured lithium-containing phosphates, lithium transition metal oxides, and their respective modified compounds. Examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxides (such as LiCoO2), lithium nickel oxides (such as LiNiO2), lithium manganese oxides (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxides, lithium manganese cobalt oxides, lithium nickel manganese oxides, lithium nickel cobalt manganese oxides (such as LiNi 1 / 3Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon.

[0125] It should be noted that, in some embodiments, the pre-coating layer may include both the carbon coating layer and the active particle coating layer, and the relative positions of the pre-coating layer, the active particle coating layer and the protective coating layer are not limited.

[0126] In some embodiments, the current collector comprises:

[0127] Substrate; the material of the substrate includes one or more of aluminum foil, nickel foil and titanium-nickel alloy; and

[0128] The protective coating is located on at least one side of the substrate, the protective coating comprises polydioxolane and lithium salt; the mass proportion of the lithium salt in the protective coating is 0.5%-8%; the lithium salt comprises one or more of lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide and lithium bis(pentafluoroethanesulfonyl)imide; the thickness of the protective coating is 50nm-800nm; the mass proportion of polydioxolane in the protective coating is 92%-99.5%; aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is charge attraction between the aluminum ions and the surface of the protective coating adjacent to the substrate.

[0129] In some embodiments, the current collector comprises:

[0130] The substrate material includes one or more of aluminum foil, nickel foil and titanium-nickel alloy;

[0131] A protective coating, located on at least one side of the substrate, the protective coating comprising polydioxolane and a lithium salt; the mass proportion of the lithium salt in the protective coating is 0.5%-8%; the lithium salt comprises one or more of lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide and lithium bis(pentafluoroethanesulfonyl)imide; the thickness of the protective coating is 50nm-800nm; the mass proportion of the polydioxolane in the protective coating is 92%-99.5%; aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is charge attraction between the aluminum ions and the surface of the protective coating adjacent to the substrate; and

[0132] The carbon coating is located between a substrate and a protective coating, aluminum ions are adsorbed at the interface between the carbon coating and the protective coating, and there is a charge adsorption effect between the aluminum ions and the surface of the protective coating on the side adjacent to the carbon coating; or the carbon coating is located on the side of the protective coating away from the substrate, aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is a charge attraction effect between the aluminum ions and the surface of the protective coating on the side adjacent to the substrate; the thickness of the carbon coating is 1μm-10μm; the carbon coating comprises a first conductive agent and a first binder, the mass ratio of the first conductive agent to the first binder is (1-19):1, the first conductive agent comprises one or more of superconducting carbon fiber, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, and the first binder comprises one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0133] In some embodiments, the current collector comprises:

[0134] The substrate material includes one or more of aluminum foil, nickel foil and titanium-nickel alloy;

[0135] A protective coating, located on at least one side of the substrate, the protective coating comprising polydioxolane and a lithium salt; the mass proportion of the lithium salt in the protective coating is 0.5%-8%; the lithium salt comprises one or more of lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide and lithium bis(pentafluoroethanesulfonyl)imide; the thickness of the protective coating is 50nm-800nm; the mass proportion of the polydioxolane in the protective coating is 92%-99.5%; aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is charge attraction between the aluminum ions and the surface of the protective coating adjacent to the substrate; and

[0136] The active particle coating is located between the substrate and the protective coating, aluminum ions are adsorbed at the interface between the active particle coating and the protective coating, and there is a charge adsorption effect between the aluminum ions and the surface of the protective coating adjacent to the active particle coating; or it is located on the side of the protective coating away from the substrate, aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is a charge attraction effect between the aluminum ions and the surface of the protective coating adjacent to the substrate; the thickness of the active particle coating is 2μm-20μm; the active particle coating comprises active material particles, a second conductive agent and a second binder, and the volume average particle size D of the active material particles is v50 is 0.2μm-4μm, and the mass ratio of the active material particles, the second conductive agent and the second binder is (50-80):(10-30):(10-20), the second conductive agent includes one or more of superconducting carbon fiber, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers, and the second binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

[0137] The second aspect of the present application provides a method for preparing the current collector of the first aspect, comprising the following steps:

[0138] A solution A containing an etchant and a solution B containing 1,3-dioxolane are prepared respectively, wherein the solution B further contains one or more of a sulfonic acid group and a sulfonic acid-like group; the solution A is coated on at least one side of a substrate precursor for etching to prepare a substrate; and the solution B is coated on the surface of the etched substrate precursor to prepare a current collector.

[0139] In the related art, aluminum foil is often used as the substrate of the positive electrode current collector. Taking aluminum foil as an example, the preparation mechanism of the current collector may be as follows: the surface of the aluminum foil has a naturally formed Al2O3 oxide layer. After solution A is coated on the surface of the aluminum foil, the etchant can etch the surface of the aluminum foil; then solution B containing 1,3-dioxolane is coated on the etched surface of the aluminum foil. Under the catalytic action of the sulfonic acid group and / or sulfonic acid-like group, the 1,3-dioxolane molecules open into rings to form long chains, and finally a protective coating is formed on a macro scale to prepare the current collector.

[0140] In some embodiments, the etchant includes a fluorine-containing aluminum sulfonate; the etchant contains aluminum ions, and when the substrate precursor is etched, the aluminum ions can be adsorbed on the surface of the substrate and evenly distributed, and after the solution B containing 1,3-dioxolane is subsequently added, the aluminum ions distributed on the substrate can adsorb 1,3-dioxolane on the surface of the substrate due to charge attraction, and a large amount of adsorbed 1,3-dioxolane undergoes ring-opening polymerization reaction under the catalysis of sulfonic acid groups or sulfonic acid-like groups; the etchant also contains sulfonic acid groups and / or sulfonic acid-like groups, which can synergistically catalyze the ring-opening polymerization reaction of 1,3-dioxolane.

[0141] In some optional embodiments, the fluorine-containing aluminum sulfonate salt includes one or more of aluminum trifluoromethanesulfonate, aluminum perfluorobutanesulfonate, and aluminum bistrifluoromethanesulfonimide.

[0142] In some optional embodiments, the mass proportion of the fluorinated aluminum sulfonate in the solution A is 2%-5%; for example, it is but not limited to 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or the range between any two of the above values. When the mass proportion of the fluorinated aluminum sulfonate in solution A is lower than the above range, the surface of the substrate cannot be fully etched, resulting in insufficient bonding strength of the protective coating; when the mass proportion of the fluorinated aluminum sulfonate in solution A is higher than the above range, too many sulfonic acid groups or sulfonic acid-like groups are introduced, and lithium salt crystals are easily formed after drying, affecting the connection of the polymer.

[0143] In some optional embodiments, the solvent of solution A includes one or more of 1,2-dimethoxyethane, diethyl ether, acetone and acetonitrile.

[0144] In some embodiments, solution B also contains lithium ions, and the lithium ions form lithium salts with at least one of the sulfonic acid groups and the sulfonic acid-like groups; by adding the lithium salt, the finally prepared protective coating also contains lithium ions, and after the current collector is prepared into a secondary battery, the lithium ions can be slowly released during the charge and discharge process of the secondary battery, thereby improving the cycle life of the secondary battery.

[0145] In some optional embodiments, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium bis(pentafluoroethanesulfonyl)imide; the lithium salt also contains sulfonic acid groups and / or sulfonic acid-like groups, which can work together with the sulfonic acid groups and / or sulfonic acid-like groups in the etchant to catalyze the ring-opening polymerization reaction of 1,3-dioxolane.

[0146] In some optional embodiments, the mass proportion of lithium salt in solution B is 2%-5%; for example, it can be but not limited to 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range between any two of the above values. When the mass proportion of lithium salt in solution B is lower than the above range, it may lead to insufficient catalytic reaction and difficulty in polymerizing 1,3-dioxolane into chains; when the mass proportion of lithium salt in solution B is higher than the above range, too much lithium salt will exist in the protective coating in the form of crystalline particles, affecting the overall flexibility of the protective coating.

[0147] In some embodiments, the etching time is 5 min-30 min; for example, it can be but not limited to 5 min, 7 min, 10 min, 13 min, 15 min, 18 min, 20 min, 23 min, 25 min, 28 min, 30 min or a range between any two of the above values. When the etching time is controlled within the above range, the substrate is effectively etched without affecting the strength of the substrate; when the etching time is lower than the above range, the substrate cannot be effectively etched; when the etching time is higher than the above range, it is easy to cause damage to the substrate and affect the strength of the substrate.

[0148] It should be noted that, in some embodiments, the step of preparing a carbon coating and / or preparing an active particle coating is also included; when preparing the carbon coating and / or the active particle coating, the conventional coating preparation method in the art can be used to prepare them; for example, a slurry can be prepared first, and then the slurry can be coated on a substrate or a protective coating, and dried to obtain the carbon coating and / or the active particle coating.

[0149] In some embodiments, the preparation method of the current collector includes: separately preparing a solution A containing an etchant and a solution B containing 1,3-dioxolane; the etchant includes a fluorinated aluminum sulfonate, the fluorinated aluminum sulfonate includes one or more of aluminum trifluoromethanesulfonate, aluminum perfluorobutanesulfonate and bis(trifluoromethanesulfonyl)imide, and the mass proportion of the fluorinated aluminum sulfonate in the solution A is 2%-5%, and the solvent of the solution A includes one or more of 1,2-dimethoxyethane, diethyl ether, acetone and acetonitrile; the solution B further includes a lithium salt, the lithium salt includes one or more of bis(trifluoromethanesulfonyl)imide lithium, bis(fluorosulfonyl)imide lithium and bis(pentafluoroethanesulfonyl)imide lithium, and the mass proportion of the lithium salt in the solution B is 2%-5%;

[0150] Applying solution A on at least one side of the surface of the substrate precursor and etching for 5-30 minutes, followed by drying to obtain a substrate;

[0151] Solution B was coated on the surface of the etched substrate precursor, left to stand at room temperature for 24 hours and then dried to obtain a current collector.

[0152] The third aspect of the present application provides a positive electrode plate, comprising the current collector of the first aspect or the current collector prepared by the method of the second aspect.

[0153] The positive electrode sheet also includes a positive electrode film layer located on at least one side of the current collector; as an example, the current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film layer is arranged on any one or both of the two opposite surfaces of the current collector.

[0154] In some embodiments, the lithium ion positive electrode active material may include positive electrode active materials for batteries that are well known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium phosphates containing olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries can also be used. These positive electrode active materials can be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523 )、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode film layer is 80-100% by weight, based on the total weight of the positive electrode film layer.

[0155] It should be noted that the battery will be accompanied by Li deintercalation and consumption during the charge and discharge process, and the molar content of Li is different when the battery is discharged to different states. In the list of positive electrode active materials in this application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.

[0156] In the list of positive electrode active materials in this application, the molar content of O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual molar content of O will fluctuate.

[0157] In some embodiments, the positive electrode film layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.

[0158] In some embodiments, the positive electrode film layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode film layer is 0-20% by weight, based on the total weight of the positive electrode film layer.

[0159] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry, wherein the positive electrode slurry has a solid content of 40-80wt%, and the viscosity at room temperature is adjusted to 5000-25000mPa·s, and the positive electrode slurry is coated on both sides of the positive electrode collector, and after drying, the positive electrode sheet is formed by cold rolling; the unit surface density of the positive electrode powder coated on one side is 12-20mg / cm 2The compaction density of the positive electrode is 3.0-3.75g / cm 3 , optional: 3.4-3.65g / cm 3 The calculation formula of the compacted density is:

[0160] Compacted density = coating surface density / (thickness of the electrode after extrusion - thickness of the current collector).

[0161] The fourth aspect of the present application provides a secondary battery, comprising the positive electrode sheet of the third aspect of the present application. The secondary battery containing the above-mentioned current collector has high safety and excellent cycle performance.

[0162] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0163] Negative electrode

[0164] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.

[0165] As an example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0166] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.

[0167] In some embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode film layer is 70-100% by weight, based on the total weight of the negative electrode film layer.

[0168] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode film layer is 0-30% by weight, based on the total weight of the negative electrode film layer.

[0169] In some embodiments, the negative electrode film layer may further include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode film layer is 0-20 weight %, based on the total weight of the negative electrode film layer.

[0170] In some embodiments, the negative electrode film layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode film layer is 0-15% by weight, based on the total weight of the negative electrode film layer.

[0171] In some embodiments, the negative electrode sheet can be prepared by the following method: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry, wherein the solid content of the negative electrode slurry is 30-70wt%, and the viscosity at room temperature is adjusted to 2000-10000mPa·s; the obtained negative electrode slurry is coated on the surfaces of both sides of the negative electrode current collector, and after a drying process, cold pressing such as rolling, a negative electrode sheet is obtained. The unit surface density of the negative electrode powder coated on one side is 75-220mg / m 2 , the compaction density of negative electrode is 1.2-2.0g / m 3 .

[0172] Electrolytes

[0173] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0174] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0175] In some embodiments, the electrolyte salt may be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte salt is generally 0.5-5 mol / L.

[0176] In some embodiments, the solvent can be selected from one or more of fluoroethylene carbonate (FEC), ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0177] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0178] Isolation film

[0179] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0180] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.

[0181] In some embodiments, the isolation film has a thickness of 3-20 μm, and optionally 5-12 μm.

[0182] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process; and the electrode assembly and the electrolyte are packaged using the battery cell packaging material of the first aspect of the present application.

[0183] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 4 The secondary battery 1 is a square structure as an example.

[0184] In some embodiments, reference Figure 5 The outer package may include a shell 11 and a cover plate 13. The shell 11 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 11 has an opening connected to the receiving cavity, and the cover plate 13 can be covered on the opening to close the receiving cavity.

[0185] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly 12. The electrode assembly 12 is encapsulated in the housing cavity. The electrolyte is infiltrated in the electrode assembly 12. The number of electrode assemblies 12 contained in the secondary battery 1 can be one or more, which can be adjusted according to needs.

[0186] In some embodiments, secondary batteries may be assembled into a battery module. The battery module may contain multiple secondary batteries, and the specific number may be adjusted according to the application and capacity of the battery module.

[0187] In the battery module, the plurality of secondary batteries may be arranged in sequence along the length direction of the battery module. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries may be fixed by fasteners.

[0188] Optionally, the battery module may further include a housing having an accommodation space, and the plurality of secondary batteries are accommodated in the accommodation space.

[0189] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0190] The battery pack may include a battery box and a plurality of battery modules disposed in the battery box. The battery box includes an upper box body and a lower box body, and the upper box body can be covered on the lower box body to form a closed space for accommodating the battery modules. The plurality of battery modules can be arranged in the battery box in any manner.

[0191] Electrical devices

[0192] In a fifth aspect, the present application provides an electrical device, which includes at least one of the secondary battery, battery module or battery pack on the fourth side of the present application. The secondary battery, battery module or battery pack can be used as a power source for the device, or as an energy storage unit for the device. The device may be, but is not limited to, a mobile device, an electric vehicle, an electric train, a ship and a satellite, an energy storage system, etc.; wherein the mobile device may include, but is not limited to, at least one of a mobile phone, a laptop computer, etc.; the electric vehicle may include, but is not limited to, at least one of a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.

[0193] The device can select a secondary battery, a battery module or a battery pack according to its usage requirements.

[0194] Figure 6 The power consumption device 2 is taken as an example. The power consumption device 2 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the high power and high energy density requirements of the device for the secondary battery, a battery pack or a battery module can be used.

[0195] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.

[0196] The beneficial effects of the present application are further illustrated below in conjunction with embodiments.

[0197] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the following will be further described in detail with reference to the embodiments and drawings. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work belong to the scope of protection of the present application.

[0198] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0199] 1. Preparation of current collector

[0200] Example 1

[0201] Aluminum trifluoromethanesulfonate (as an etchant) is dissolved in 1,2-dimethoxyethane with a mass percentage concentration controlled at 2%-5% to obtain a solution A;

[0202] Apply solution A to the surface of aluminum foil, etch for 5-30 minutes, and dry to obtain the substrate;

[0203] Dissolving lithium bis(trifluoromethanesulfonyl)imide (as lithium salt) in 1,3-dioxolane to obtain a solution B with a mass percentage concentration of 2% to 5%;

[0204] Solution B was coated on the etched surface of the substrate, and dried at room temperature for 24 hours to form a protective coating to prepare a current collector.

[0205] Example 2-39

[0206] The preparation method of the current collector in Example 2-39 is basically similar to the preparation method of the current collector in Example 1, and the main difference lies in: at least one of the type of etchant and / or its mass percentage concentration in solution A, etching time, type of lithium salt and / or its mass percentage concentration in solution B, type of substrate, and raw materials of the pre-coating layer is different. See Table 1 for details.

[0207] The current collector prepared in each of the above embodiments is measured to measure at least one of the following structural parameters: the mass ratio of lithium salt in the protective coating, the thickness of the protective coating, the mass ratio of polydioxolane in the protective coating, the thickness of the carbon coating, the mass ratio of the conductive agent and the binder in the carbon coating, the thickness of the active particle coating, the volume average particle size Dv50 of the active material particles, and the mass ratio of the active material particles and the second conductive agent and the second binder in the active particle coating. The measurement results are shown in Table 1.

[0208] Comparative Example 1

[0209] In Comparative Example 1, only aluminum foil was used as the current collector, and no protective coating or pre-coating was prepared.

[0210] The preparation parameters and structural parameters of the above embodiments and comparative examples are shown in Table 1-1 and Table 1-2.

[0211] Table 1-1

[0212]

[0213] Table 1-2

[0214]

[0215] In Table 1-1 and Table 1-2, W1 represents the mass percentage concentration of the etchant in solution A, T1 represents the etching time, W2 represents the mass percentage concentration of the lithium salt in solution B, W3 represents the mass ratio of the first conductive agent and the first binder added when preparing the carbon coating, or W3 represents the mass ratio of the active material particles, the second conductive agent and the second binder added when preparing the active particle coating; d1 represents the volume average particle size Dv50 of the active material particles in the active particle coating; SP represents carbon black; PVDF represents polyvinylidene fluoride; PTFE represents polytetrafluoroethylene; CNT represents carbon nanotube; M1 represents the mass percentage of the lithium salt in the protective coating, L1 represents the thickness of the protective coating, M2 represents the mass percentage of polydioxolane in the protective coating; L2 represents the thickness of the pre-coating layer when the pre-coating layer is the active particle coating; L3 represents the thickness of the pre-coating layer when the pre-coating layer is the carbon coating. LiTFSI represents lithium bistrifluoromethanesulfonyl imide, and LiFSI represents lithium bisfluorosulfonyl imide.

[0216] It should be noted that the mass proportion of lithium salt in the protective coating mentioned above is determined by the following method: the substrate with the protective coating is immersed in deionized water, and after ultrasonic and stirring dissolution, the lithium salt content is determined by ion chromatography.

[0217] The mass proportion of polydioxolane in the above-mentioned protective coating is determined by thermogravimetric analysis.

[0218] The thickness of the protective coating, the thickness of the carbon coating and the thickness of the active particle coating mentioned above are measured using a scanning electron microscope.

[0219] 2. Preparation of secondary batteries

[0220] 1. Preparation of positive electrode

[0221] The positive electrode active material NCM955, the conductive agent acetylene black, and the binder polyvinylidene fluoride (PVDF) are dissolved in a solvent N-methylpyrrolidone (NMP) in a weight ratio of 96.5:1.5:2, and the positive electrode slurry is obtained after being fully stirred and mixed. Then, the positive electrode slurry is evenly coated on the double-side surfaces of the current collector prepared in the above-mentioned embodiments and comparative examples, and then dried, cold pressed, and cut to obtain the positive electrode sheet.

[0222] 2. Preparation of negative electrode sheet

[0223] The active material graphite, the conductive agent acetylene black, the thickener sodium carboxymethyl cellulose (CMC), and the binder are dissolved in the solvent deionized water in a weight ratio of 95:1:2:1, and then evenly mixed with the solvent deionized water to prepare a negative electrode slurry. The negative electrode slurry is coated on both sides of the copper foil, dried, and then cold-pressed and cut to obtain a negative electrode sheet.

[0224] 3. Use PE film as diaphragm.

[0225] 4. Preparation of Electrolyte

[0226] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte; the concentration of LiPF6 in the electrolyte is 1 mol / L.

[0227] 5. Preparation of Cells

[0228] The positive electrode sheet, the isolation film, and the negative electrode sheet are stacked in order, so that the isolation film is placed between the positive and negative electrode sheets to play an isolating role, and then they are wound to obtain a bare battery cell, the tabs are welded to the bare battery cell, and the bare battery cell is placed in an aluminum shell and baked at 80°C to remove water, and then the electrolyte is injected and sealed to obtain an uncharged battery; the uncharged battery then undergoes static standing, hot and cold pressing, formation, shaping, capacity testing and other processes in sequence to obtain a lithium-ion battery product.

[0229] 3. Secondary battery performance test

[0230] 1. Capacity test

[0231] At room temperature of 25℃, the battery capacity was tested according to the following process: the battery was cross-current discharged to 2.8V at a rate of 0.33C, and after 5 minutes, it was charged to 4.25V at a rate of 0.33C. The charging capacity was recorded as the battery capacity.

[0232] 2. Cycle life test

[0233] At 25°C, the battery was charged to 80% SOC at a constant current of 0.5C, and then charged to 4.25V at a constant current and voltage of 0.33C. After standing for 5 minutes, it was discharged to 2.8V at a rate of 0.5C to complete a charge and discharge cycle. The number of cycles when the battery capacity decayed to 80% SOC was recorded.

[0234] 3. Impedance test

[0235] The DC resistance of the battery before cycling and when the battery capacity decays to 80% SOC is tested respectively, and the increase in impedance before and after the battery cycling is calculated; the DC impedance test methods before cycling and when the capacity decays to 80% SOC are as follows:

[0236] At 25°C, the battery capacity was calibrated to 50% SOC by constant current 0.33C discharge, and after 5 minutes of storage, the battery was discharged at 4C for 30 seconds, and the voltage difference before and after 4C discharge was recorded. The ratio of the voltage difference to the 4C current was the DC impedance. The performance test results of the above embodiments and comparative examples are shown in Table 2.

[0237] Table 2

[0238]

[0239]

[0240] From the comparison of the results of Examples 1-39 and Comparative Example 1 in Table 2, it can be seen that the use of the current collector of the present application can improve the safety and cycle life of the secondary battery and reduce the impedance of the secondary battery.

[0241] The difference between Examples 1-7 is that the thickness of the protective coating is different. The thickness of the protective coating in Example 2 is the smallest, and the thickness of the protective coating in Example 7 is the largest. Comparing the results of Examples 1-7, it can be seen that the capacity in Example 2 is the largest, and the capacity in Example 7 is the smallest. Compared with Examples 2 and 7, the number of cycles in Examples 1 and Examples 3-6 is significantly increased, and the impedance increase is significantly reduced. The technicians analyzed that the reason may be that: when the thickness of the protective coating is too small, it is beneficial to increase the battery capacity, but the electrolyte may easily corrode the aluminum foil, resulting in a significant deterioration in the battery cycle performance and impedance. When the thickness of the protective coating is too large, the electrolyte is not easy to corrode the aluminum foil, but the insufficient conductivity of the protective coating itself may cause the battery impedance to increase, and the excessive thickness of the protective coating will also deteriorate the battery capacity. In addition, the excessive thickness of the protective coating will also affect electron transmission and deteriorate the cycle life.

[0242] The difference between Example 1 and Examples 8-13 is that the mass proportion of lithium salt in the protective coating is different. The mass proportion of lithium salt in Example 8 is the smallest, and the mass proportion of lithium salt in Example 13 is the largest; compared with Example 8 and Example 13, the number of cycles in Examples 1 and Examples 9-12 is significantly increased, and the impedance increase is significantly reduced; technicians analyzed that the reason may be due to: when the mass proportion of lithium salt in the protective coating is too small, it means that too little lithium salt is added during the preparation of the protective coating, resulting in too little addition of sulfonic acid groups and / or sulfonic acid-like groups that catalyze the ring-opening polymerization of 1,3-dioxolane, which may cause 1,3-dioxolane to fail to fully polymerize to form a dense protective coating, thereby worsening the protective effect; when the mass proportion of lithium salt in the protective coating is too large, too much lithium salt may exist in the protective coating in the form of crystalline particles, resulting in insufficient flexibility of the protective coating, which also worsens the protective effect.

[0243] The difference between Examples 14-19 is that the thickness of the carbon coating is different. The thickness of the carbon coating in Example 15 is the smallest, and the thickness of the carbon coating in Example 19 is the largest. Compared with Example 1, the number of cycles in Examples 14-19 increases, and the impedance increase decreases, indicating that the anti-corrosion protection effect on the substrate can be further improved by adding a carbon coating, and the conductivity of the current collector is improved, thereby reducing the impedance of the secondary battery and improving the cycle performance of the secondary battery. Compared with Examples 15 and 19, the number of cycles in Examples 14 and Examples 16-18 increases significantly, and the impedance increase decreases; the technicians analyze that the reason may be due to: when the thickness of the carbon coating is insufficient, the protective ability of the carbon coating against the substrate may be relatively limited; when the carbon coating is too thick, on the one hand, the carbon coating contains more conductive agents, and the conductive agents (such as carbon black) may have an adsorption effect on the electrolyte, resulting in the failure of some electrolytes to play a role, making the cycle life relatively worse; on the other hand, the carbon coating contains more conductive agents, and the conductive agent as a whole has a larger specific surface area. During the cycle, under the influence of the potential, there may be accumulation of byproducts on the surface of the conductive agent, resulting in a relative deterioration of the impedance. The capacity in Example 15 is significantly reduced, which may be because when the carbon coating is too thick, it will occupy the limited space inside the battery and significantly deteriorate the battery capacity.

[0244] The difference between Example 14 and Examples 20-23 is that the mass ratio of the conductive agent to the binder in the carbon coating is different, which is the smallest in Example 20 and the largest in Example 23; compared with Examples 20 and 23, the number of cycles in Examples 14 and Examples 21-22 is significantly increased, and the impedance increase is significantly reduced. The technicians analyzed that the reason may be that: when the amount of conductive agent in the carbon coating is insufficient, the conductivity of the carbon coating may be poor, thereby significantly deteriorating the impedance and cycle performance of the secondary battery; when the amount of binder in the carbon coating is insufficient, the carbon coating may fall off, thereby significantly deteriorating the cycle performance and impedance.

[0245] The difference between Examples 26-30 is that the thickness of the active particle coating is different, with the smallest thickness in Example 27 and the largest thickness in Example 30. Compared with Example 1, the number of cycles in Examples 26-30 increases and the impedance increase decreases, indicating that the corrosion protection effect on the substrate can be further improved and the impedance increase can be improved by adding an active particle coating. Compared with Examples 27 and 30, the number of cycles in Examples 26 and Examples 28-29 increases significantly and the impedance increase decreases, which may be due to: when the thickness of the active particle coating is insufficient, the protective ability of the active particle coating against the substrate may be relatively limited; when the active particle coating is too thick, on the one hand, the non-conductive material in the active particle coating increases, which may cause the impedance to deteriorate relative to the situation where the thickness of the active particle coating is small; on the other hand, the active particle coating contains more active material particles, and the active material particles have a large specific surface area as a whole, which may lead to an increase in side reactions, thereby causing a relative deterioration in the cycle life. The capacity decrease in Example 30 may be due to the fact that when the active particle coating is too thick, the inactive material in the coating increases, resulting in a decrease in capacity.

[0246] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0247] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be construed as limiting the scope of the patent application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent application shall be subject to the attached claims.

Claims

1. A current collector, characterized in that: include: Base material; as well as A protective coating is disposed on at least one side of the substrate, wherein the protective coating comprises polydioxolane.

2. The current collector according to claim 1, characterized in that The protective coating further comprises lithium ions and at least one of a sulfonic acid group and a sulfonic acid-like group, wherein the lithium ions form a lithium salt with at least one of the sulfonic acid group and the sulfonic acid-like group; Optionally, the mass proportion of the lithium salt in the protective coating is 0.5%-8%, optionally 2%-5%; Optionally, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium bis(pentafluoroethanesulfonyl)imide.

3. The current collector according to any one of claims 1 to 2, characterized in that: The thickness of the protective coating is 50nm-800nm, and can be optionally 300nm-500nm.

4. The current collector according to any one of claims 1 to 3, characterized in that: The mass proportion of the polydioxolane in the protective coating is 92%-99.5%, and can be optionally 95%-98%.

5. The current collector according to any one of claims 1 to 4, characterized in that: Aluminum ions are adsorbed at the interface between the substrate and the protective coating, and there is charge attraction between the aluminum ions and the surface of the protective coating adjacent to the substrate.

6. The current collector according to any one of claims 1 to 4, characterized in that: The current collector further includes a pre-coating layer; Optionally, the pre-coating layer comprises at least one of the following features: (1) The pre-coating layer is located between the substrate and the protective coating layer; (2) the pre-coating layer is located between the substrate and the protective coating layer, aluminum ions are adsorbed at the interface between the pre-coating layer and the protective coating layer, and there is a charge adsorption effect between the aluminum ions and the surface of the protective coating layer adjacent to the pre-coating layer; (3) The pre-coating layer is located on a side of the protective coating layer away from the substrate; (4) The pre-coating layer is located on a side of the protective coating layer away from the substrate, aluminum ions are adsorbed at the interface between the substrate and the protective coating layer, and there is a charge attraction between the aluminum ions and a surface of the protective coating layer adjacent to the substrate.

7. The current collector according to claim 6, characterized in that The pre-coating layer comprises a carbon coating; Optionally, the material of the carbon coating has at least one of the following characteristics: (1) The thickness of the carbon coating is 1 μm-10 μm, and can be 1 μm-5 μm; (2) The carbon coating comprises a first conductive agent and a first binder; Optionally, the mass ratio of the first conductive agent to the first bonding agent is (1-19):1; Optionally, the first conductive agent includes one or more of superconducting carbon fiber, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; Optionally, the first binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

8. The current collector according to any one of claims 6 to 7, characterized in that: The pre-coating layer includes an active particle coating; Optionally, the active particle coating has at least one of the following characteristics: (1) The thickness of the active particle coating is 2 μm-20 μm; (2) The active particle coating comprises active material particles, a second conductive agent and a second binder; Optionally, the volume average particle size Dv50 of the active material particles is 0.2 μm-4 μm; Optionally, the mass ratio of the active material particles, the second conductive agent and the second binder is (50-80):(10-30):(10-20); Optionally, the second conductive agent includes one or more of superconducting carbon fiber, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; Optionally, the second binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.

9. A method for preparing a current collector according to any one of claims 1 to 8, characterized in that: The steps include: A solution A containing an etchant and a solution B containing 1,3-dioxolane are prepared respectively; the solution B further contains one or more of a sulfonic acid group and a sulfonic acid-like group; The solution A is coated on at least one side of the surface of the substrate precursor and then etched to prepare the substrate; Solution B is coated on the surface of the etched substrate precursor to prepare the current collector.

10. The method for preparing a current collector according to claim 9, characterized in that: The solution A comprises at least one of the following conditions: (1) The etchant comprises a fluorinated aluminum sulfonate; Optionally, the fluorine-containing aluminum sulfonate salt includes one or more of aluminum trifluoromethanesulfonate, aluminum perfluorobutanesulfonate, and aluminum bistrifluoromethanesulfonimide; (2) The mass proportion of the fluorinated aluminum sulfonate in the solution A is 2%-5%; (3) The solvent of the solution A includes one or more of 1,2-dimethoxyethane, diethyl ether, acetone and acetonitrile.

11. The method for preparing a current collector according to any one of claims 9 to 10, characterized in that: The solution B further comprises lithium ions, and the lithium ions form a lithium salt with at least one of the sulfonic acid group and the sulfonic acid-like group; Optionally, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium bis(pentafluoroethanesulfonyl)imide; Optionally, the mass proportion of the lithium salt in the solution B is 2%-5%.

12. The method for preparing a current collector according to any one of claims 9 to 11, characterized in that: The etching time is 5 min-30 min.

13. A positive electrode plate, characterized in that: The invention comprises a current collector as claimed in any one of claims 1 to 8 or a current collector prepared by the method as claimed in any one of claims 9 to 12.

14. A secondary battery, characterized in that: The secondary battery comprises the positive electrode sheet as claimed in claim 13.

15. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 14.

Citation Information

Patent Citations

  • High-power high-energy iron phosphate lithium battery and preparation method thereof

    CN101593846A

  • MOF modified polyether solid-liquid mixed electrolyte as well as preparation method and application thereof

    CN115939508A

  • Method of improving fast-chargeability of a lithium battery

    US20190379021A1

  • Secondary battery and preparation method therefor

    US20220328863A1

  • Coated lithium electrodes

    US6537701B1

Cited By

  • Positive plate, preparation method thereof and solid-state battery

    CN121192170A